Case report: potential treatment of metastatic amphicrine carcinoma of the rectum with FOLFOXIRI chemotherapy. Issue 11 (24th November 2020) - Tamura, Nobumasa; Honma, Yoshitaka; Sekine, Shigeki; Tsukamoto, Shunsuke; Hirano, Hidekazu; Okita, Natsuko; Shoji, Hirokazu; Iwasa, Satoru; Takashima, Atsuo; Kato, Ken; Boku, Narikazu
ABSTRACT: Amphicrine carcinoma (AmC) is a unique epithelial tumor displaying exocrine and endocrine features in the same cell. It shows an adenocarcinoma-like cellular form and has endocrine granules. There are few reports describing chemotherapy for AmC. Here, we describe a case with metastatic AmC from the rectum that was treated with FOLFOXIRI chemotherapy. A 64-year-old man was diagnosed with a submucosal lesion on the scar produced after an endoscopic mucosal resection, which had been performed for adenocarcinoma of the rectum 2 years before. The endoscopic submucosal dissection revealed AmC. The abdominoperineal resection including lymph nodes dissection was performed. Thereafter, computed tomography showed multiple liver metastases, and FOLFOXIRI was administered. The best overall response was partial response, and progression-free survival was 8.7 months. After 16.0 months since first-line chemotherapy the patient died. We can therefore conclude that FOLFOXIRI may be effective for AmC of the rectum.